The Legal Status of Islands and Other Features and the China's Unreasonable Claim on the Nine-dash Line in South China Sea Under the Arbitration Award in the Philippines v. China Case - Vinh, Nguyen Tien (VNU Journal of Science: Legal Studies; Vol 36 No 1, 2020)
In the context of the long, complex disputes in Bien Dong (South China Sea) and the emergence of the use of force risks therefor, a long term solution based on a system of approaches and measures on deferent diplomatic, economic, and legal levels must be available. On the legal level, the Article analyzes the main contents of the Arbitration Award in the Philippines v. China Case regarding the status of islands and other features and the China's unreasonable claim on the nine-dash line and its actions in the South China Sea. Since then, the Article suggests the comments on the effects and consequences of the Award in light of the general perception that this Award is an important victory of international law in general and of the Law of the Sea in particular, this also is the victory of the countries, including Vietnam against China's unjustified unilateral claims and acts in the South China Sea. Keywords: South China sea; the arbitration award on South China sea, legal status of islands, the nine-dash line. References: [1] PCA Case Nº 2013-19, The South China Sea Arbitration, Award of 12 July 2016, https://pcacases.com/web/sendAttach/2086. [2] Nikos Papadakis, The International Legal Regime of Artificial Islands, Sijthoff - Leyden, 1977. [3] Convention on the Territorial Sea and the Contiguous Zone, Geneva 29 April 1958, United Nations, Treaty Series , vol. 516, p. 205. [4] Convention on the Continental Shelf, Geneva, 29 April 1958, United Nations, Treaty Series , vol. 499, p. 311. [5] United Nations Convention on the Law of the Sea, Montego Bay 10 December 1982. [6] Van Dyke, M. Jon and Bennett, Dale (1993), Islands and the Delimitation of Ocean Space in the South China Sea, 10 Ocean Yearbook. [7] Jonathan I. Charney (1999), Rocks That Cannot Sustain Human Habitation, American Journal of International Law, 93 A.J.I.L. 863. [8] Continental Shelf Area between Jan Mayen and Iceland (Jan Mayen Continental Shelf), Report and Recommendations to the Government of Iceland and Norway of the Conciliation Commission of 19-20 May 1981 in 62 International Law Reports (1981), p. 108. [9] D.W. Bowett (1979), The Legal Regime of Islands in International Law; E.D. Brown (1978), Rockall and the Limits of National Jurisdiction of the UK: Part 1, Marine Policy Vol. 2, p. 181 at pp. 206-207; J.M. Van Dyke & R.A. Brooks (1983), Uninhabited Islands: Their Impact on the Ownership of the Oceans’ Resources, Ocean Development and International Law, Vol. 12, , Nos. 3-4, p. 265; R. Kolb (1994), The Interpretation of Article 121, Paragraph 3 of the United Nations Convention on the Law of the Sea: Rocks Which Cannot Sustain Human Habitation or Economic Life of Their Own, French Yearbook of International Law, Vol. 40, 1994, p. 899; D. Anderson (2002), Islands and Rocks in the Modern Law of the Sea, in United Nations Convention on the Law of the Sea 1982: A Commentary, Vol. VI, pp. 307-21; J.L. Jesus, Rocks (2003), New-born Islands, Sea Level Rise, and Maritime Space, in J. Frowein, et al., eds., Negotiating for Peace, p. 579. [10] North Sea Continental Shelf Cases, Para 57. [11] Tunisia Libya Case, Para. 128. [12] Case Concerning Delimitation of the Maritime Boundary in the Gulf of Maine Area, (U.S. v. Canada), I.C.J. Reports 1984, p. 222. [13] PCA Case Nº 2013-19, The South China Sea Arbitration, Award of 12 July 2016. Truy cập tại đường link: https://pcacases.com/web/sendAttach/2086. [14] Note Verbal No. CML/8/2011 (14 April 2011) from the Permanent Mission of the People’s Republic of China to the UN Secretary-General with regard to the joint submission made by Malaysia and Viet Nam to the Commssion on the Limites of Continental Shefl, Annex I, Doc. A23; Foreign Ministry Spokesperson Hua Chunying's Remarks on Relevant Issue about Taiping Dao, 06/03/2016: www.fmprc.gov.cn/mfa_eng/xwfw_665399/s2510665401/t1369189.shtml. [15] Daniel Schaerffer, The Legacy of the Nine -Dashed Line: Past, Present and Future in International Workshop Paracel and Spratly Archipelagos History Truth, Danang, 19-21/4/2014: http://pdu.edu.vn/a/index.php?dept=20&disd=&tid=4921. [16] Note Verbal No. CML/17/2009 (7 May 2009) from the Permanent Mission of the People’s Republic of China to the UN Secretary-General with regard to the joint submission made by Malaysia and Viet Nam to the Commssion on the Limites of Continental Shefl: https://www.un.org/Depts/los/clcs_new/submissions files/mysvnm33_09/chn_2009re_mys_vnm_e.pdf. [17] Commission on the Limits of the Continental Shelf (CLCS) Outer limits of the continental shelf beyond 200 nautical miles from the baselines: Submissions to the Commission: Joint submission by Malaysia and the Socialist Republic of Vietnam. [18] http://www.un.org/Depts/los/clcs_new/submissiosfiles/submission_mysvnm_33_2009.htm.